PENGARUH LABELISASI HALAL DAN TINGKAT RELIGIUS KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK WARDAH OLEH MUSLIMAH MILENIAL - Selvi Putri Nengsih; Henryanto Abaharis (LP2M Universitas Bina Bangsa, 2024)
The purpose of this research is to determine the influence of halal labeling and the level of religiousness among consumers on the purchasing decisions of Wardah products by millennial Muslim women. This research utilizes a quantitative approach. Data collection involves distributing questionnaires to 89 respondents using probability sampling techniques. Respondents' answers are processed using SPSS. The results of this study indicate that halal labeling and the level of consumer religiosity have a positive and significant impact on the purchasing decisions of Wardah products by millennial Muslim women